1999
DOI: 10.1126/science.286.5446.1946
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Bone Formation in Vitro and in Rodents by Statins

Abstract: Osteoporosis and other diseases of bone loss are a major public health problem. Here it is shown that the statins, drugs widely used for lowering serum cholesterol, also enhance new bone formation in vitro and in rodents. This effect was associated with increased expression of the bone morphogenetic protein-2 (BMP-2) gene in bone cells. Lovastatin and simvastatin increased bone formation when injected subcutaneously over the calvaria of mice and increased cancellous bone volume when orally administered to rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
1,320
9
52

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,607 publications
(1,429 citation statements)
references
References 19 publications
48
1,320
9
52
Order By: Relevance
“…They are in use as anticholesterol drugs since the 80s. The focus was shifted to their osteoinductive properties by the initial research started by Mundy et al [3]. All the above mentioned osteoinductive and osteoconductive actions of simvastatins were similar to the maximal doses of BMP2; because they induce Heat Shock Protien 27, enhance mRNA expression for BMP2, Alkaline Phospahatase (ALP), Osteocalcin and Vascular Endothelial Growth Factor by inhibition of Rho-associated Kinase activity in osteoblasts, bone marrow cells and stem cells in vitro and in vivo in rats and in rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are in use as anticholesterol drugs since the 80s. The focus was shifted to their osteoinductive properties by the initial research started by Mundy et al [3]. All the above mentioned osteoinductive and osteoconductive actions of simvastatins were similar to the maximal doses of BMP2; because they induce Heat Shock Protien 27, enhance mRNA expression for BMP2, Alkaline Phospahatase (ALP), Osteocalcin and Vascular Endothelial Growth Factor by inhibition of Rho-associated Kinase activity in osteoblasts, bone marrow cells and stem cells in vitro and in vivo in rats and in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [2] showed that BMP-2 causes differentiation of a multipotential stem cell line into osteoblast-like cells. To discover small molecules that induce BMP-2, Mundy et al [3] examined more than 30,000 compounds from a collection of natural products and tested the effects of compounds on the expression of the BMP-2 gene. They identified a statin, a common cholesterol-lowering drug that inhibits hepatic hydroxymethylglutaryl coenzyme A (HMG-CoA) reductase, the rate-limiting enzyme in the mevalonate pathway, as the only product in the collection that specifically increased expression of the BMP-2 gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The devices described in the present work released simvastatin acid at a rate of approximately 36.5 ng/hr into 5 ml of PBS. To stimulate bone formation in animals, Mundy et al (1999) injected 1−10 mg/kg/day subcutaneously over the calvaria of mice for 5 days. Assuming 30 g animals, up to approximately 300 μg of simvastatin was administered each day.…”
Section: Discussionmentioning
confidence: 99%
“…Statins offer additional benefits, such as promotion of new blood vessel growth (Kureishi et al, 2000) and anti-inflammatory effects (Davignon and Laaksonen, 1999). Most relevant to the present work, Mundy's group originally demonstrated that statins induce expression of bone morphogenetic protein 2 (BMP-2) and that they stimulate bone formation on the calvaria of mice following daily subcutaneous injections (Mundy et al, 1999). Subsequent studies have shown that oral dosing with simvastatin increases cancellous bone volume in rats (Maeda et al, 2001), and it also increases transverse area of fracture callus as well as mechanical properties compared to controls (Skoglund et al, 2002).…”
Section: Introductionmentioning
confidence: 97%